2015
DOI: 10.1007/s00259-015-3037-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk stratification using metabolic parameters of 18F-FDG PET/CT in patients with endometrial cancer

Abstract: MTV and TLG of primary endometrial cancer show better correlations with clinicopathological features and are more useful for differentiating high-risk from low-risk carcinoma than SUVmax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 25 publications
6
35
1
Order By: Relevance
“…In line with this finding, adjusted for the preoperative biopsy risk assessment, MTV independently predicted deep myometrial invasion and lymph node metastases ( Table 3), suggesting that MTV may improve the preoperative identification of high-risk patients and the ability to tailor surgical and systemic therapies accordingly. Our results are in line with a recent study of 56 endometrial carcinoma patients (23) emphasizing MTV and TLG as significant predictors of several clinicopathologic characteristics and superior to SUV max in differentiating high-risk from low-risk patients. Also two studies of 76 endometrial carcinoma patients each (13,28) suggested that MTV is a promising marker for lymph node metastases and poor outcome.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with this finding, adjusted for the preoperative biopsy risk assessment, MTV independently predicted deep myometrial invasion and lymph node metastases ( Table 3), suggesting that MTV may improve the preoperative identification of high-risk patients and the ability to tailor surgical and systemic therapies accordingly. Our results are in line with a recent study of 56 endometrial carcinoma patients (23) emphasizing MTV and TLG as significant predictors of several clinicopathologic characteristics and superior to SUV max in differentiating high-risk from low-risk patients. Also two studies of 76 endometrial carcinoma patients each (13,28) suggested that MTV is a promising marker for lymph node metastases and poor outcome.…”
Section: Discussionsupporting
confidence: 91%
“…As opposed to our proposed cutoff, a recent smaller study of 56 patients proposed a cutoff of 9.4 mL for MTV for differentiation between high-risk and low-risk tumors (based on surgicopathologic assessment). This differing result is possibly explained by a larger proportion of patients with an advanced FIGO stage in the cohort and differing definitions of high-and lowrisk groups (23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies, some authors found SUVmax correlates with histologic grade (22,23) and some did not (24,25). In our study, we found that grade 2 tumors had statistically not important but higher SUVmax values than grade 1 tumors and statistically significantly higher SUVmax values than grade 3 tumors.…”
Section: Discussionsupporting
confidence: 72%
“…The cut-off value was determined by referring to data reported in previous studies. [18][19][20][21][22][23] Each VOI for calculating MTV and TLG was first placed manually, paying careful attention not to include high physiological uptake, and then MTV was automatically extracted on a workstation. The summed MTV was produced as the WB-MTV.…”
Section: Measurements Of Positron Emission Tomography/ct Parametersmentioning
confidence: 99%